GERAK TANGAN SEBAGAI ISYARAT DALAM MASYARAKAT JEPANG DAN MASYARAKAT INDONESIA - Maharani Patria Ratna (Universitas Diponegoro, 2014)
Abstract This article describes phenomenon of similarities and differences gestures which have similarities and differences in the interpretation of the meaning of Japan society and Indonesia society. In Japan society and Indonesia society, equations of motion cues with similar meaning indicating similarities mindsets. In contrast, differences in gestures with different meanings show different mindset. This paper also describes some cases phenomenon of gesture interpretation misunderstandings caused by cultural differences between speaker and listener. To learn a language, is to learn the culture contained therein Keywords: gestures, mindsets, society, culture, phenomenon